PENGARUH PEMBACAAN AL-QURAN BIN NAGHAM (TILAWAH) PADA KETENANGAN JIWA SANTRI PONPES LSQ AR-RAHMAH BANTUL - Andy Rosyidin (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
The Qur'an is interesting to study because it has secrets that many people don't know about without being aware of. One of them is about the element of ash-Shifa, namely the Koran as a medicine / antidote as stipulated in the Koran Surah Al-Isra ': 82. In some interpretations the purpose of the drug or the antidote is not limited to disturbances in the body but dzohir / physical also feltthe presence of these miracles. Various methods can be done by someone to get the miracle of al-Qur'an as ash-Shifa, one of them is by reciting the Qur'an method. Namely reading the Koran by using tones and charts (tausyih) which have been commonly used in MTQ starting from method. Namely reading the Koran by using tones and charts (tausyih) which the baby and its derivation to the level of the Jiharkah song. In processing this article the authors used a descriptive-qualitative method that is by describing the evidence that the Qur'an read by the recitation method has an influence on the psychology (peace of mind) of readers and listeners. Then use interviewtechniques as a data collection. As for the scope of this study, the author focuses on the students at the Islamic Boarding School LSQ ar-Rahmah Bantul Yogyakarta.